Origin and Persistence of Markings in a Long-Term Photo-Identification Dataset Reveal the Threat of Entanglement for Endangered Northern Bottlenose Whales (Hyperoodon ampullatus) - Feyrer, Laura Joan; Stewart, Madison; Yeung, Jas; Soulier, Colette; Whitehead, Hal (Frontiers in Marine Science, 2021)
Photo-identification methods depend on markings that are stable over time. Using a large dataset of photographs taken over a 31-year period, we evaluate the reliability, rate of change and demographic trends in different mark types on northern bottlenose whales (Hyperoodon ampullatus) in the Endangered Scotian Shelf population, and assess the prevalence and severity of anthropogenically caused markings. Only fin notches and back indentations were stable over long timescales, leading to 48% of the overall population being assessed as reliably marked. Males and mature males were found to have higher incidence of most mark types compared to females and juveniles. The proportion of reliably marked individuals increased over time, a trend that should be accounted for in any temporal analysis of population size using mark-recapture methods. An overall increase in marked individuals may reflect the accumulation of scars on an aging population post whaling. Anthropogenic markings, including probable entanglement and propeller-vessel strike scars, occurred at a steady rate over the study period and were observed on 6.6% of the population. The annual gain rate for all injuries associated with anthropogenic interactions was over 5 times the annual potential biological removal (PBR) calculated for the endangered population. As entanglement incidents and propeller-vessel strike injuries are typically undetected in offshore areas, we provide the first minimum estimate of harmful human interactions for northern bottlenose whales. With low observer effort for fisheries across the Canadian Atlantic, photo-identification offers an important line of evidence of the risks faced by this Endangered whale population.